Prophylactic low dose ketamine and ondansetron for prevention of shivering during spinal anaesthesia - B Shakya; A Chaturvedi; B P Sah (Wolters Kluwer Medknow Publications, 2010)
Background: Perioperative shivering is a common problem during anaesthesia. Apart from physical warming many drugs have also been used for prevention of shivering. Ketamine has been used for preventing shivering during anaesthesia in doses of 0.5 to 0.75mg kg -1 , but even these doses causes too much sedation and hallucination. Ondansetron (8 mg) has been recently evaluated for its perioperative antishivering effect in patients under anaethesia. Present study was conducted to evaluate the efficacy and safety of low dose Ketamine (0.25mg kg -1 ) and Ondansetron (4 mg) for prevention of shivering during spinal anaesthesia. Patients & Methods: Total 120 patients undergoing lower abdominal surgery under spinal anaesthesia were included. 3ml of hyperbaric bupivacaine 0.5% was used for spinal anaesthesia. After intrathecal injection, the patients were randomly divided in 3 groups of 40 each who received Ketamine 0.25mg kg -1 or Ondansetron 4mg IV or Saline. Vitals, temperature and shivering scores were recorded every 5 minutes. Side effects i.e. hypotension, nausea and vomiting, sedation and hallucinations were also recorded. Results: Fall in temperature was more significant in saline and ondansetron group (gp) than in ketamine group at all time interval. Out of 40 patients, shivering was maximum & seen in 17 patients (42.50%) in saline gp, 4 patients (10%) in ondansetron gp and in only 1patient (2.5%) in ketamine gp. Odd ratio of ketamine, ondansetron and saline are 1, 4.33 and 28.33 respectively which means that shivering in saline gp was 28.83 times higher than ketamine gp and 6.65 times higher than in ondansetron .Shivering rate was 4.33 times higher in ondansetron gp than in ketamine gp. Hypotension was lowest in ketamine gp (10%) in comparison to ondansetron gp (22.5%) and saline gp. (20%). Mild sedation was seen in almost all (95%) patients in ketamine gp, Conclusion: Prophylactic low dose ketamine (0.25mg kg -1 ) and Ondansetron (4mg) significantly decreased shivering in patients undergoing spinal anaesthesia without significant side effects.